2023
DOI: 10.1007/s42773-023-00232-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application to temperate grasslands: challenges and opportunities for delivering multiple ecosystem services

Abstract: Grasslands (natural, semi-natural and improved) occupy approximately one-third of the terrestrial biosphere and are key for global ecosystem service provision, storing up to 30% of soil organic carbon (SOC). To date, most research on soil carbon (C) sequestration has focused on croplands where the levels of native soil organic matter (SOM) are typically low and significant potential exists to replenish SOM stocks. However, with the renewed push to achieve “net zero” C emissions by 2050, grasslands may offer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…We found that the soil pH under different concentration Cd treatments did vary significantly for using the GPE Jiaosu and Jiaosu residue. Meanwhile, the application of GPE Jiaosu and Jiaosu residue modified the basic soil property, including the contents of SOC, TN, AN, and TP, when exposed to different levels of Cd stresses, which was similar to the effect of biochar and compost on soil fertility (Brown et al 2023;Huo et al 2023).…”
Section: CDmentioning
confidence: 70%
See 1 more Smart Citation
“…We found that the soil pH under different concentration Cd treatments did vary significantly for using the GPE Jiaosu and Jiaosu residue. Meanwhile, the application of GPE Jiaosu and Jiaosu residue modified the basic soil property, including the contents of SOC, TN, AN, and TP, when exposed to different levels of Cd stresses, which was similar to the effect of biochar and compost on soil fertility (Brown et al 2023;Huo et al 2023).…”
Section: CDmentioning
confidence: 70%
“…The strategies and application advantages of using fermented products for solving the two major problems (agricultural and forestry wastes as well as phytoremediation of heavy metal pollution) faced by current environmental improvement and agricultural and forestry development. Brown et al 2023). Therefore, if we can explore some substances or materials to remedy the soil avoiding or alleviating above disadvantages, it will be important, necessary, and urgent for soil improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations involving genes responsible for producing DAO (AOC1 on chromosome 7) can increase the susceptibility to histamine-intolerance development [218]. Some drugs, including NSAIDS, antidepressants, immunomodulators, antiarrhythmics, and other substances (e.g., acetylcysteine, clavulan acid, metoclopramide, and verapamil), may decrease the threshold of tolerance to histamines [219]. Alcohol consumption, in particular, red wine, is a powerful inhibitor of DAO because it also contains, in addition to high levels of histamine, other classes of biogenic amines, such as tyramine and sulfites, which compete with the histamine for binding to the active site of the enzyme [220].…”
Section: Abstention From Histamine-rich Food Consumptionmentioning
confidence: 99%
“…Comparing the q max = 8.08 mg/g obtained for PWJ biochar with typical reports for active carbon, clays, and nanoparticles of composites, the value reported herein is small. However, the biochar adsorbents obtained from waste contribute to reducing the bio-accumulate process in the environment [44] and offer an alternative for carbon storage [94].…”
Section: Isothermal Study Of Mo Adsorption On Pjw Biocharmentioning
confidence: 99%